Analysis of commercial glasses with different strengthening treatments: Emphasis on the tin side, defects, structure connectivity and cracking behavior - Andrew Barron (Journal of Non-Crystalline Solids, 2019)
Tin side of commercial glasses with different strengthening treatments (i.e. tempered, heat strengthened, chemically strengthened) and without treatment (annealed soda-lime glass) have been compositional and surface characterized and then, compared with Gorilla Glass®. Surface flaws from the strength treatment were observed in thermally treated samples by AFM. Raman studies show differences in the network connectivity (Q2/Q1 ratio) because the different structures caused by the treatments. XPS was used to evaluate the oxidation state of the tin and compare the variations through the different treatments. Complementary, a study about the crack behaviour using a Vickers indenter was performed; different cracking pattern was obtained for float soda-lime glass in comparison with Gorilla Glass®. In addition, the IQ2:IQ1 ratio as determined from Raman spectroscopy correlates with crack size from indentations.